Management Issues in Myasthenia Gravis Patients Living With HIV: A Case Series and Literature Review - Heckmann, Jeannine M.; Marais, Suzaan (Frontiers in Neurology, 2020)
South Africa is home to more than seven million people living with human immunodeficiency virus (HIV) and a high prevalence of tuberculosis. Human immunodeficiency virus–infected individuals may develop myasthenia gravis (MG), which raises questions regarding their management. An MG database, with 24 years of observational data, was audited for HIV-infected persons. Case reports of MG in HIV-infected persons were reviewed. We identified 17 persons with MG and HIV infection. All had generalized MG with a mean age at onset of 37.8 years. Eleven had acetylcholine receptor antibody–positive MG; one had antibodies against muscle-specific kinase. Six developed MG prior to HIV infection (mean CD4+ 361 cells/mm3); four worsened <6 months of starting antiretrovirals. Eleven developed MG while HIV-infected (mean CD4+ 423 cells/mm3); five presented with mild MG; three in MG crisis requiring rescue therapies (intravenous immune globulin or plasma exchange and/or intravenous cyclophosphamide). Two were diagnosed with HIV infection and MG at the same time. Fifteen required maintenance steroid-sparing immune therapies, predominantly azathioprine, or methotrexate. Plasma HIV viral loads remained below detectable levels on antiretrovirals during immunosuppressant treatment. Over the average follow-up of 6 years, 10 achieved minimal manifestation status, and the remainder improved to mild symptoms. Three cases had tuberculosis before MG, but none developed tuberculosis reactivation on immunosuppressive therapy; one used isoniazid prophylaxis. Herpes zoster reactivation during treatment occurred in one. Conclusions include the following: MG in HIV-infected patients should be managed similarly to individuals without HIV infection; half develop moderate–severe MG; MG symptoms may worsen within 6 months of antiretroviral initiation; safety monitoring must include plasma HIV viral load estimation. Isoniazid prophylaxis may not be indicated in all cases.